Determinant Of The Covid-19 Adaptation Readiness Model (Journal of Pharmaceutical Negative Results, 2023)
Objective: Currently, the spread of the COVID-19 virus has decreased significantly. However, the Indonesian government continues to create various policies to adapt to unpredictable conditions caused by the pandemic. Therefore, applying and maintaining community adaptation is paramount to increasing readiness in dealing with repeated COVID-19. This study aims to find out determinant of COVID-19 adaptation readiness of the community to coexist with COVID-19.Methods: We used a cross-sectional method with multivariate analysis using a logistic regressiontest. The sample is people who have been exposed to Covid-19 in the July-August 2021 period that met the inclusion criteria in the Auxiliary Health Center, East Pamulang, Banten. Of the 264 positive Covid-19 patients registered at the auxiliary health center, only 231 people were willing to fill out the questionnaire. The data collection used direct questionnaires from Desember 2022-Januari 2022.Result : The analysis of the five factors shows that the dominant factor on readiness to adapt to Covid-19 was social support with OR = 1.194; 95% CI =1.117-1.276 and a Hosmer value of 0.377, which means the model used in this study is fit.Conclusion : Public Understanding of the pandemic conditions, which promotes mutual support and alerts in the health protocols, along with other measures in increasing the immunity system, such as adequate nutrition in preventing COVID-19, is essential to prepare the community to adapt to the new habits in coexisting with the Covid-19 pandemic.